Progress in high-temperature plasma research at NCBJ (former IPJ) in Poland - Sadowski, M.J. (Вопросы атомной науки и техники, 2012)
This invited lecture presents the most important results of theoretical and experimental studies of hightemperature plasma, which were performed at the NCBJ (former IPJ) in Otwock-Swierk, Poland, during recent two years. The research activity included: Studies of fast electrons and X-rays in Z-pinch and Tokamak devices; Research on applications of solid-state nuclear track detectors for detection of fast ions and neutrons emitted from plasma in experimental facilities of Z-pinch, Tokamak and ICF type; Investigations of high-temperature plasma streams and their interactions with solid targets; Ultra-high vacuum arc deposition of thin metallic films; Selected studies on plasma engineering of solid surfaces. The formation of the NCBJ (on Sept. 1, 2011) and its successive reorganization (on Jan. 1, 2012) led to the separation of the Division of Plasma Studies (TJ5) which is concentrated on high-temperature plasmas within frames of domestic and international research programs.